USE OF ELECTROENCEPHALOGRAPHY AND FACE BIOMETRICS FOR EVALUATION OF CHRISTMAS AROMATIC COMPOUNDS - Paluchová, Johana; Berčík, Jakub; Prokeinová, Renáta Benda (PEOPLE: International Journal of Social Sciences, 2019)
The Christmas time is traditionally associated with the purchase of gifts and a specific shopping atmosphere. While we may not perceive it, it is also the result of multiple senses´ influencing at the same time that we either perceive or do not influence affect our mood, decision making, memories and overall feeling of buying. An important component of shopping atmosphere is aromatic air. Although the smell has in terms of perception (human perception) relatively low share in relation to sight or hearing. Its significance mainly lies in impact on memory and creating of associations. The research integrates the measurements of importance to use specific Christmas aromatic compounds for clients and their influence of human sense. Research objects were chosen six samples typical for Christmas time. The main methods needed for obtained data in consumer neuroscience survey were used one biometrics (Facial Biometrics Recognition) and one neuroimaging (mobile Electroencephalograph) techniques in laboratory conditions. Except these, we verified three hypotheses by ANOVA and logistic regression statistics methods. The main goal of this research was a revelation of actual impact on micro emotions, valence, attention, emotional interest, frustration, relaxation, and engagement of clients/consumers.